Non-steroidal mineralocorticoid receptor antagonists in cardiorenal disease . (17th June 2022) - Pandey, Arjun K; Bhatt, Deepak L; Cosentino, Francesco; Marx, Nikolaus; Rotstein, Ori; Pitt, Bertram; Pandey, Ambarish; Butler, Javed; Verma, Subodh
Abstract: Despite existing treatments, patients with heart failure and chronic kidney disease (CKD) remain at high risk for adverse outcomes and progression to end-stage disease. Steroidal mineralocorticoid receptor antagonists (MRAs) such as spironolactone and eplerenone reduce mortality but remain under-prescribed due to the perceived risk of hyperkalaemia and hormonal side effects. The discovery of non-steroidal MRAs represents a major new dimension in cardiorenal disease therapy. Non-steroidal MRAs have high affinity and specificity for the mineralocorticoid receptor (MR) and differ from both steroidal agents and each other with respect to important physiochemical, pharmacodynamic, and pharmacokinetic parameters. Similar to their steroidal counterparts, they have beneficial anti-inflammatory, anti-remodelling, and anti-fibrotic properties in the kidneys, heart, and vasculature. There are several non-steroidal MRAs under development and clinical assessment; of these, only esaxerenone and finerenone are approved for treatment globally. In Japan, esaxerenone is approved for essential hypertension and has been studied in diabetic nephropathy. Compared with steroidal MRAs, finerenone more potently inhibits MR co-regulator recruitment and fibrosis and distributes more evenly between the heart and kidneys. The landmark Phase III trials FIGARO-DKD and FIDELIO-DKD demonstrated that finerenone-reduced major kidney and cardiovascular events on top of maximally tolerated renin–angiotensin–aldosterone system inhibition in patients with CKD associated with Type 2 diabetes. Non-steroidal MRAs are currently under evaluation in heart failure and for synergistic treatment with sodium–glucose contransporter 2 inhibitors. These ground-breaking agents could become an important therapy across the spectrum of cardiorenal disease. Graphical Abstract: Graphical Abstract Non-steroidal mineralocorticoid antagonists (MRAs) reduce adverse remodelling, inflammation, and fibrosis in the heart, kidneys, and vasculature. Finerenone has been shown to improve cardiovascular and kidney outcomes in patients with chronic kidney disease and Type 2 diabetes. Non-steroidal MRAs are currently being investigated in other settings such as heart failure. Audio Abstract: